periuretheral endometriosis-case report - tofiloska, valentina (Medicinski časopis, 2022)
ABSTRACT The aim of this paper is to present a rare case of periureteral endometriosis in an adult patient and to emphasize the importance of suspected urinary tract endometriosis and the important role of CT of the pelvis in making an accurate diagnosis of this rare disease. The authors present a rare case of periureteral endometriosis with symptoms primarily arising from ovarian endometriosis. The diagnosis of periureteral endometriosis was determined on the basis of CT of the small pelvis and abdomen. Key words: endometriosis, CT, ovarian endometriosis